2014
DOI: 10.3109/0886022x.2014.976160
|View full text |Cite
|
Sign up to set email alerts
|

Effects and safety of iron-based phosphate binders in dialysis patients: a systematic review and meta-analysis

Abstract: Aim: To assess the effects and safety of iron-based phosphate binders in adult patients receiving dialysis. Methods: We electronically searched MEDLINE, EMBASE, CENTRAL, and CBM for randomized controlled trials about iron-based phosphate binders in adult dialysis patients. Study quality was assessed using the criteria outlined in the Cochrane Handbook for Systematic Reviews of intervention. Meta-analysis was conducted by RevMan 5.3. Results: Eight studies with 2018 participants were eligible for our meta-analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
(91 reference statements)
1
7
0
Order By: Relevance
“…Our results are consistent with previous systematic reviews that also report reduced serum and urinary phosphate with phosphate-binding agents 19 21 , 50 52 . This systematic review, however, included only patients with CKD stages 3–5 not on dialysis and involved more recent RCTs, including several recent placebo-controlled studies.…”
Section: Discussionsupporting
confidence: 90%
“…Our results are consistent with previous systematic reviews that also report reduced serum and urinary phosphate with phosphate-binding agents 19 21 , 50 52 . This systematic review, however, included only patients with CKD stages 3–5 not on dialysis and involved more recent RCTs, including several recent placebo-controlled studies.…”
Section: Discussionsupporting
confidence: 90%
“…Many pair meta‐analyses have been conducted to compare performances between 2 treatments for hyperphosphatemia patients with CKD. Zhai et al, for example, evaluated the effectiveness and safety between iron‐based phosphate binders and placebo in treating adult hyperphosphatemia patients with CKD, concluding that iron‐based phosphate binders outperformed placebo. Wang et al reported that calcium acetate showed better efficacy compared with calcium carbonate by conducting a meta‐analysis.…”
Section: Discussionmentioning
confidence: 99%
“…62,68 Calcium-based binders, which are some of the most commonly used binders and available as generic/ over-the-counter formulations (e.g., calcium carbonate), can improve hypocalcemia but also can contribute to increased calcium loading (hypercalcemia), a risk factor for CV calcification and mortality. 62 Iron-based agents (e.g., ferric citrate) can improve anemia but can result in iron overload and associated toxicity 68,70 ; an exception is sucroferric oxyhydroxide, a newer agent with minimal systemic absorption and no evidence of iron accumulation in a phase 3 clinical study. [71][72][73][74] Sucroferric oxyhydroxide also tends to have a favorable side effect profile on the GI system and is one of the most efficacious binders currently on the market.…”
Section: Phosphate Bindersmentioning
confidence: 99%